A Green and Highly Efficient Naphthalimide Visible Photoinitiator with an Ability Initiating Free Radical Polymerization under Air. Issue 24 (9th November 2018) - Yang, Jianjing; Xu, Can; Xiong, Ying; Wang, Xiaoling; Xie, Yujun; Li, Zhen; Tang, Hongding
Abstract: A visible photoinitiator, 2‐(2‐(1, 3‐dioxo‐6‐(piperidin‐1‐yl)‐1 H ‐benzo[de]‐isoquinolin‐2(3 H )‐yl)ethoxy)ethyl acrylate (ND‐O‐EA), for attenuating the oxygen inhibition in the free radical polymerization, is designed and synthesized. The results show that it has an outstanding ability to overcome oxygen inhibition demonstrated by the fact that no induction period is observed during the free radical polymerization of the acrylate in the air. A possible preferred intramolecular hydrogen‐abstraction reaction in which a peroxyl radical regenerates a new carbon radical through a stable six‐member ring intermediate, should correspond to its anti‐oxygen capacity. After 1 min of irradiation under air atmosphere, the double‐bond conversion of 1, 6‐hexanediol diacrylate in the ND‐O‐EA system can be up to 13.3%, while the camphorquinone‐ N ‐methyldiethanolamine (CQ‐MDEA) system is about 8.0%, and the phenylbis(2, 4, 6‐trimethylbenzoyl)phosphine oxide (BAPO) is only 0.13%. Furthermore, as a one‐component polymerizable photoinitiator, the mass fraction of the extracted ND‐O‐EA is about 6.2% with respect to the initial quality after photopolymerization. Abstract : A one‐component visible photoinitiator 2‐(2‐(1, 3‐dioxo‐6‐(piperidin‐1‐yl)‐1 H ‐benzo[de]‐isoquinolin‐2(3 H )‐yl)ethoxy)ethyl acrylate, is designed and prepared. It shows an outstanding free radical polymerization initiating ability. It exhibits an outstanding ability to overcome oxygen inhibition and initiates the acrylate monomers under air. It also shows excellent migration stability.